EFEKTIVITAS MODEL PEMBELAJARAN INKUIRI TERHADAPHASIL BELAJARSHOOTINGBASKET PESERTA DIDIKSMA PGRI 1 PONTIANAK - Elisius, Elisius; Simanjuntak, Victor Gaperius; Haetami, Mimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this study was to determine the effectiveness of the inquiry learning model on the learning outcomes of basketball shooting in the class X SMA PGRI 1 pontianak students. This research method used an experimental method with a quasy experiment research design that was a non equivalent control group design. The population in this study were class X students with 70 people. Sampling using non probability sampling techniques in the form of saturated sampling. Data analysis using t-test. The results showed the value of the initial test (pretest) was the lowest value of 27 and the highest score of 81 with the average score of 49.88, while the final test score (posttest) was obtained by the lowest score of 45 and score 100 with an average value of 78.54 can be seen an increase with a difference in the average value of 28.66 with a percentage of 57.46%. Based on the results above, it showed that the inquiry learning model was very effective on the learning outcomes of basketball shooting in class X SMA PGRI 1 Pontianak students.Keywords: Basketball,Model of Inquiry Learning, Shooting